2017
DOI: 10.3389/fnins.2017.00730
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Neural Control of Sympathetic Nerve Activity: Status Report and Directions for Future Research

Abstract: Sympathetic nerve activity (SNA) contributes appreciably to the control of physiological function, such that pathological alterations in SNA can lead to a variety of diseases. The goal of this review is to discuss the characteristics of SNA, briefly review the methodology that has been used to assess SNA and its control, and to describe the essential role of neurophysiological studies in conscious animals to provide additional insights into the regulation of SNA. Studies in both humans and animals have shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 197 publications
(291 reference statements)
1
41
0
Order By: Relevance
“…Central command evokes parallel modifications of motor and autonomic functions during exercise, and excites the central cardiovascular pathways containing the RVLM. 27 We previously reported that central command-elicited sympathoexcitation becomes exaggerated in CHF by demonstrating that renal sympathoexcitation in response to electrical stimulation of the mesencephalic locomotor region (MLR), stimulation of which evokes fictive locomotion under paralysis, was larger in rats with CHF than that in controls. 28 Subsequently, we demonstrated that administration within the RVLM of Tempol, a SOD mimetic, reduced MLR stimulation-elicited sympathoexcitation in CHF, suggesting the role of superoxide overproduction in the RVLM in enhancing central command-elicited sympathetic outflow in CHF.…”
Section: Zimmerman Et Al Showed That Hypertension Caused By Chronic mentioning
confidence: 98%
“…Central command evokes parallel modifications of motor and autonomic functions during exercise, and excites the central cardiovascular pathways containing the RVLM. 27 We previously reported that central command-elicited sympathoexcitation becomes exaggerated in CHF by demonstrating that renal sympathoexcitation in response to electrical stimulation of the mesencephalic locomotor region (MLR), stimulation of which evokes fictive locomotion under paralysis, was larger in rats with CHF than that in controls. 28 Subsequently, we demonstrated that administration within the RVLM of Tempol, a SOD mimetic, reduced MLR stimulation-elicited sympathoexcitation in CHF, suggesting the role of superoxide overproduction in the RVLM in enhancing central command-elicited sympathetic outflow in CHF.…”
Section: Zimmerman Et Al Showed That Hypertension Caused By Chronic mentioning
confidence: 98%
“…A basal level of sympathetic activity, or sympathetic tone, together with opposing activity from the parasympathetic nervous system, ensures bodily homeostasis. Sympathetic tone may rise on a short timescale in response to a physiological demand (for example, exercise or stress) [18,19], or over a long timescale, in a sustained manner, under pathological conditions such as hypertension and chronic heart disease [20,21]. Sympathetic tone is initially set by neurons present in the brain and spinal cord [22], with the sympathetic ganglionic neurons acting as the final regulatory element determining the output of the sympathetic circuit.…”
Section: Introductionmentioning
confidence: 99%
“…A basal level of sympathetic activity, or sympathetic tone, together with opposing activity from the parasympathetic nervous system, ensures constant bodily homeostasis. Sympathetic tone may rise on a short timescale in response to a physiological demand (for example, exercise or stress) [18, 19], or over a long timescale, in a sustained manner, under pathological conditions such as hypertension and chronic heart disease [20, 21]. Sympathetic tone is initially set by neurons present in the brain and spinal cord [22], with the sympathetic ganglionic neurons acting as the final regulatory element determining the output of the sympathetic circuit.…”
Section: Introductionmentioning
confidence: 99%